Coral Reef Bleaching Crisis: Impacts on Indonesia's Marine Ecosystems and Coastal Economy - Angelina Dwi Susanti; Friska Silaban; Lambok Febryan Aritonang; Yessi Tri Yosika br Sitompul (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2025)
Indonesia, as the world’s largest archipelagic state, is home to vast marine biodiversity, particularly coral reefs that support more than 25% of marine species despite covering less than 1% of the ocean floor. However, these vital ecosystems are increasingly threatened by climate-induced stressors such as rising sea surface temperatures and anthropogenic pressures including pollution, destructive fishing practices, and coastal development. The most visible manifestation of this crisis is coral bleaching, which compromises reef health and biodiversity. This study aims to explore the ecological and economic impacts of coral reef bleaching in Indonesia and propose strategic responses for sustainable marine governance. Employing a descriptive qualitative approach, the research draws upon peer-reviewed literature, government reports, and international assessments to analyze the drivers, consequences, and policy implications of coral bleaching. Findings reveal that elevated sea temperatures caused by global warming and phenomena like El Niño have led to mass coral bleaching events, reducing coral cover, disrupting marine food chains, and impairing ecosystem services. Socio-economically, the bleaching crisis has diminished fisheries productivity, reduced marine tourism revenue, and heightened economic vulnerability in coastal communities. Coral reef degradation also weakens natural coastal defenses, increasing exposure to storm damage. The study concludes that integrated policy interventions centered on conservation, community-based management, and climate adaptation are critical for reversing coral decline. Strengthening marine spatial planning, enforcing sustainable fishing regulations, and promoting blue economy principles can help safeguard coral reefs and enhance the resilience of Indonesia’s coastal economy.